2019
DOI: 10.1080/14017431.2019.1583363
|View full text |Cite
|
Sign up to set email alerts
|

ST2 in heart failure with preserved and reduced ejection fraction

Abstract: Objectives. Soluble suppression of tumorigenecity 2 (sST2) is prognostic in acute and chronic heart failure with reduced ejection fraction (HFrEF) but less studied in HF with preserved EF (HFpEF). We evaluated sST2 concentrations, correlations with biomarkers and echocardiographic measures of diastolic and systolic function, and associations with outcomes in HFpEF and HFrEF. Design and results. A total of 193 subjects from three different cohorts were included. Eighty-six HFpEF patients were obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 49 publications
(61 reference statements)
8
29
3
5
Order By: Relevance
“…However, contrary to our expectations, HFpEF patients evidenced low levels of sST2 similar to the control group. This finding also matches former studies, which reported lower levels of sST2 in HFpEF compared to HFrEF [28]. Further and bigger studies are required to verify these findings and help in explaining the underlying mechanisms of these results.…”
Section: Discussionsupporting
confidence: 92%
“…However, contrary to our expectations, HFpEF patients evidenced low levels of sST2 similar to the control group. This finding also matches former studies, which reported lower levels of sST2 in HFpEF compared to HFrEF [28]. Further and bigger studies are required to verify these findings and help in explaining the underlying mechanisms of these results.…”
Section: Discussionsupporting
confidence: 92%
“…Большой интерес представляет выявленная взаимосвязь NGAL и sST2, маркера, дополнительно использованного нами в качестве раннего и более точного диагностического признака ХСН. sST2 в ряде литературных источников рассматривается как независимый от функционального состояния почек маркер сердечной недостаточности, причем его диагностическая ценность велика как в отношении ХСН с сохраненной, так и сниженной ФВ ЛЖ [18]. Описана его независимая, ввиду экстракардиального происхождения, роль в активации провоспалительного механизма при формировании эндотелиальной дисфункции и миокардиального стресса в условиях коморбидности [19].…”
Section: Discussionunclassified
“…Indeed, HF patients who were attained lowered levels of sST2 (<35ng/mL) and NT-proBNP (<1000 pg/mL) in contrast to those have haven higher levels of both biomarkers (≥35ng/mL and ≥1000 pg/mL, respectively) during treatment had been found improved survival and decreased need for re-admission [36,37] . In fact, multiple biomarker model based on both sST2 and NT-pro-BNP was able not just predict clinical outcomes during HF therapy, but yet to improve accuracy of prognostication for both HFpEF and HFrEF [38] . Although circulating levels of sST2 were predominantly associated with all-cause mortality and non-CV death in HF out-patients showing strong association with systemic inflammation and malnutrition, while NT-proBNP levels were associated with CV death and re-admission [39] , the combined use of both biomarkers for personifying optimization of HF care appears to be promising.…”
Section: Soluble St2 As Potential Target Of In-tervention In Hf Patientsmentioning
confidence: 99%